Research priorities in the Tasmanian devil facial tumour debate - Obendorf, David L.; McGlashan, Neil D. (European Journal of Oncology and Environmental Health, 2008)
Against a résumé of current understanding of the nature, incidence and spread of the Tasmanian devil facial tumour (DFT), this script is presented with the aim of drawing attention to two particular research priorities; both are currently under-rated and under-funded. This wildlife disease was first recognised over ten years ago in the extreme north-east region of Tasmania. The invariably fatal, infectious neoplasm has affected devil populations covering two-thirds of the island of Tasmania and official estimates recognise that over half of Tasmania’s devil population, initially estimated at ~150,000 animals, have died as a direct result of the neoplasm’s transmission between wild devils. A significant turning point in defining the pathobiology of this disease was the identification of the near identical determinants of the key histocompatibility genes amongst the DFT-affected eastern Tasmanian devil populations and of the clone of neoplastic cells that is the transmissible agent of this disease. Genotyping now represents the best diagnostic tool for detecting individual devils with dissimilar immunogenetic determinants. Currently the transmissible tumour is entering the geographically separate western devil population; the population offering the greatest prospect of individuals with innate immunogenic resistance to DFT. This research warrants the very highest priority so that its potential to save the species is fully explored. A second research area, all but neglected, is a truthful investigation of the local environmental conditions that preceded the index outbreak within the high density devil population in north-east Tasmania. Based on current knowledge of this unusual new neoplasm, it is becoming increasingly likely that the genesis and effective transmission of this disease was the fateful culmination in a cascade of anthropogenic land-use activities and can more specifically be linked to a toxin-related aetiology occurring in a wild, carrion-feeding marsupial that had reached unprecedented numbers by the 1990s. The spontaneous genesis for this transmissible cell clone commenced in a devil population that already had considerable loss of genetic diversity. Understanding the sudden emergence of a transmissible cancer within a species surely warrants greater attention.